ENSURING SAFE MOTHERHOOD IN CONFLICT: EVALUATING MATERNAL HEALTH INTERVENTIONS DURING THE BOKO HARAM CRISIS IN BORNO STATE, NIGERIA - Mukhtar, Falmata; Muhammad Lawan, Abdulmalik; Muhammad Lawan, Hauwa; Ahmed Gazali, Waziri; Waziri, Muhammad (African Journal of Social and Behavioural Sciences, 2025)
Pregnant women are disproportionately affected during insurgencies, experiencing restricted access to maternal healthcare. This study examined how Boko Haram Insurgency (BHI) constrained maternal healthcare utilisation and how women adapted to challenges in accessing services in Borno State, Nigeria. Data collection involved administering questionnaires to women of childbearing age in Dikwa, Gwoza, and Magumeri, as well as conducting interviews with healthcare providers and community members. Pearson’s correlation coefficient was used to evaluate the relationship between health facility damage and maternal service utilisation. The analysis revealed that most women were aged 32-49 years (30.6%), had 5-6 children (37.3%), lacked formal education (36.7%), and were unemployed (60.7%). The insurgency impeded access to maternal healthcare, with one-third of respondents not receiving adequate antenatal care due to poor roads, distance, lack of spousal permission, and fear of being attacked. Skilled deliveries at birth decreased to less than half. Non-governmental organisations were the primary providers of maternal healthcare in the affected areas, offering antenatal, postnatal, and delivery services. In conclusion, maternal healthcare utilisation was constrained, and essential services, such as caesarean sections, were inaccessible due to limited medical equipment. This study recommends funding rural healthcare facilities, training providers, implementing maternal healthcare services, including antenatal, emergency obstetric, and postnatal care, and enhancing community outreach programs to reduce maternal mortality in rural regions.